Medieval landscapes - Gardiner, Mark (Landscape history after Hoskins, 2007)
"The medieval period was at the centre of W.G. Hoskins concerns: the period when his 'palimpsest' of the English landscape was, if not quite wiped clean, very thoroughly overwritten. The essays here demonstrate how researchers have moved beyond issues of describing and 'reading' the landscape to address the social and ideological - as well as economic - functions of landscapes, and to seek explanations for regional difference."--P. [4] of cover.